2021
DOI: 10.1101/2021.03.12.21253448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection and risk of clinical sequelae during the post-acute phase: a retrospective cohort study

Abstract: Objective: Clinical sequelae have not been well characterized during the post-acute phase of SARS-CoV-2 among adults 18 to 65 years old, and this study sought to fill that gap by evaluating excess risk and relative hazards for developing incident clinical sequelae during the post-acute phase. Design: Retrospective cohort study including three propensity-matched groups. Setting: This study merged three data sources from a large United States health plan: a large national administrative claims database, an outpa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…15 Interestingly, recent data from Denmark suggest limited post-acute complications following non-hospitalised COVID-19; 19 this is in contrast to a recent study using US health insurance data which found raised risks of a range of outcomes among a relatively young cohort with mostly (92%) non-hospitalised COVID-19 disease, compared with both the general population and people with a record of other viral lower respiratory tract infections. 14 Our data showed that COVID-19 hospitalised patients were more likely to have baseline comorbidities than general population controls, reflecting known associations between comorbidities and risks of severe COVID-19 outcomes. 6 Differences in outcomes between hospitalised patients and general population controls might therefore reflect baseline differences not fully captured in our adjustment models, and might also reflect a generic adverse effect of hospitalisation.…”
Section: Findings In Context Of Literature and Explanationsmentioning
confidence: 57%
See 1 more Smart Citation
“…15 Interestingly, recent data from Denmark suggest limited post-acute complications following non-hospitalised COVID-19; 19 this is in contrast to a recent study using US health insurance data which found raised risks of a range of outcomes among a relatively young cohort with mostly (92%) non-hospitalised COVID-19 disease, compared with both the general population and people with a record of other viral lower respiratory tract infections. 14 Our data showed that COVID-19 hospitalised patients were more likely to have baseline comorbidities than general population controls, reflecting known associations between comorbidities and risks of severe COVID-19 outcomes. 6 Differences in outcomes between hospitalised patients and general population controls might therefore reflect baseline differences not fully captured in our adjustment models, and might also reflect a generic adverse effect of hospitalisation.…”
Section: Findings In Context Of Literature and Explanationsmentioning
confidence: 57%
“…Another US study limited to people aged <65 years also found excess risks of a range of clinical outcomes ascertained from health insurance data among people with a record of SARS-CoV-2 infection. 14 A UK study of routinelycollected primary care and hospitalisation data described raised rates of all-cause hospital admission and death among patients discharged following a COVID-19 hospitalisation; the authors also noted raised risks of adverse respiratory and cardiovascular sequalae among the selected outcomes investigated. 15 Only a general population comparator was used, making it difficult to disentangle risks specific to COVID-19 from those associated with hospitalisation more generally; furthermore, a hospitalised cohort is likely to have been more prone to health problems at the outset than the general population comparator group.…”
Section: Introductionmentioning
confidence: 99%
“…Es deutet sich jedoch an, dass ca. 5 % der Patienten mit COVID-19 einen bildgebend darstellbaren Residualbefund aufweisen [6]. Ob sich hieraus therapeutische Konsequenzen ergeben, wird Gegenstand dieser Untersuchungen sein.…”
Section: Merkeunclassified
“…14 In another retrospective cohort study of three data sources from a large United States health plan, among 193 113 COVID-19 patients aged ≤65 years, NOD was the sixth most common post-acute clinical sequelae over a median follow-up of 2.9 months. 15 Possible mechanisms explaining the occurrence of NOD with SARS-CoV-2 infection during the acute phase are cytolytic effects of the virus on pancreatic β-cells, 16 activation of the hypothalamic-pituitary-adrenal and sympathoadrenal axes causing an increase in counterregulatory hormones, activation of the renin-angiotensin system resulting in unopposed deleterious actions of angiotensin II, and enhanced autoimmunity. 17,18 However, it is yet to be determined whether these mechanisms persist in the post-acute phase for the development of NOD in long COVID.…”
mentioning
confidence: 99%
“…22 The COVID-19 pandemic has now persisted for over a year, and researchers across the globe are studying its long-term effects. 2,[12][13][14][15]23,24 It is now high time to consider NOD as a metabolic clinical sequela of SARS-CoV-2 infection to understand the role of COVID-19 in driving the diabetes pandemic.…”
mentioning
confidence: 99%